PASUWITAN: PERKAWINAN SEDULUR SIKEP - Kushidayati, Lina (Sabda: Jurnal Kajian Kebudayaan, 2015)
Samin people are communities who follow the teaching of Ki Samin Surosentiko. They live in north coast of Java Island. As other Javanese people, they speak Javanese although mostly in ngoko style compared to their fellow Javanese who concern about language hierarchy. This article discusses marriage ceremony among the Samin people consisting of several steps: nyumuk, ngendek, nyuwito-ngawulo and paseksen. The marriage ceremony was held in the modest style but rich in meaning. The center of the marriage ceremony is the groom’s vow before the bride’s parents to be a husband. The vow is in simple Javanese language. According to Samin people, marriage ceremony is personal matter that needs no government involvement. Thus they do not register their marriage.